2019
DOI: 10.1038/s41372-019-0557-9
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of transcutaneous bilirubin on covered skin in preterm and term newborns receiving phototherapy using a JM-105 bilirubinometer

Abstract: Objective Determine the suitability of transcutaneous bilirubin (TCB) as a tool to assess the effectiveness of phototherapy on patched skin. Study design A prospective observational study was conducted. We covered a fragment of skin (sternum) with a photoopaque patch. Several simultaneous TCB and TSB measurements were performed with the JM-105 bilirubinometer. Bland and Altman test evaluated the agreement between bilirubin levels. Result A total of 217 patients were studied, 48.8% were preterm. The mean differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 23 publications
1
7
0
1
Order By: Relevance
“…After initiation of phototherapy and at a greater degree of prematurity, TcB-TSB agreement worsened. This is consistent with previous research that showed greater agreement between TcB and TSB prior to initiating phototherapy using the JM-103 and JM-105 devices [12, 20, 21]. As in prior studies, we saw no appreciable difference whether TcB was measured at the forehead or sternum prior to phototherapy [11, 14]; however, after the initiation of phototherapy, the current study suggests that the forehead may be the more preferred site for TcB measurement when using the JM-105 device.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…After initiation of phototherapy and at a greater degree of prematurity, TcB-TSB agreement worsened. This is consistent with previous research that showed greater agreement between TcB and TSB prior to initiating phototherapy using the JM-103 and JM-105 devices [12, 20, 21]. As in prior studies, we saw no appreciable difference whether TcB was measured at the forehead or sternum prior to phototherapy [11, 14]; however, after the initiation of phototherapy, the current study suggests that the forehead may be the more preferred site for TcB measurement when using the JM-105 device.…”
Section: Discussionsupporting
confidence: 93%
“…As such, TSB measurements should be used to make clinical decisions after the initiation of phototherapy, especially since most preterm infants start phototherapy after the first or second day of life. As a potential solution to the underperformance of TcB after initiation of phototherapy, for example, some small studies in term and preterm infants explored the effectiveness of measuring TcB on covered skin [20, 24]. A similar approach, with a larger sample size, should be considered in preterm infants, to determine the effectiveness of TcB after phototherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have noted variability between TcB and TSB in preterm infants undergoing phototherapy, but it was not significantly affecting management decisions in most studies [ 5 , 14 , 15 ]. Studies that assessed TcB on patched sternal skin vs. light-exposed skin of preterm infants undergoing phototherapy noted that patch TcB is more accurate and reliable to predict TSB [ 9 , 17 , 21 , 22 ]. Some studies found TcB tends to drift away from TSB levels when the TSB level exceeds 15 mg/dL even if measured in unexposed skin [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…This corroborates that there is a strong agreement present. The mean difference between TSB and TcB in preterm neonates before phototherapy is 0.64 mg/dl [95%: 0.13-1.14] in Posada et al using JM-105 [ 14 ]. The slightly higher accuracy of Posada et al could be secondary to the difference in the gestational age distribution and racial difference.…”
Section: Discussionmentioning
confidence: 99%